La experiencia estética de lo sublime en la danza butoh en comunicación con la naturaleza salvaje (Itinera, 2021)
This article proposes a reflection on the aesthetic experience of the sublime, today, in the practice of butoh dance performed in wild environments, and how this experience can help us to appreciate nature, something very important due to the ecological catastrophe which we face and for which we are responsible. First, we will approach to the category of the sublime from Longinus, Burke, and Kant. Second, we will review and update this category by applying it to a contemporary artistic context: butoh dance. We will be guided by three ideas to establish the relationship between the sublime and butoh: absolute, dissolution and death. Third, in order to get closer to the meeting space between butoh and sublime experience, we will offer a definition of «wild environment», trying to overcome the dichotomy between nature and artifice, thus bridging the separation between human and nature. Precisely, we will come to the conclusion that the communication or union of the body with the environment (both wild) is the gateway to the experience of the sublime as part of a state of consciousness and perception that entails admiration for the mystery of the forces that animate the world.
Keywords: dance, butoh, performance, sublime